Commemorative Street Naming of Historical Figures as Cultural Memory and Representation in Banyumas Regency - Oktaviana, Ika; Junawaroh, Siti (Faculty of Humanities, Diponegoro University, 2023)
Street naming is commonly used to give directions to some places. Moreover, street names can be used to memorialize some figures, for instance, historical figures. In this case, Banyumas Regency, one of the regencies in Indonesia, mostly creates street names by implementing historical figure names. Consequently, this paper aims to explore commemorative street naming revealing historical figures as cultural memory and representation in Banyumas Regency. Specifically, this paper examines the classification of the historical figures created as street names and their historical relations to the Banyumas Regency, whether connected or not. This research applied a descriptive qualitative method. The data were collected from multiple sources and analyzed by identifying the commemorative street names related to each figure's historical figures and historical background in Banyumas Regency. In this investigation, the findings show that the commemorative street names of the historical figures in Banyumas Regency applied four historical figure name classifications: heroes, religious figures, political figures, and others. The dominant street names of historical figures come from the hero names. Moreover, the street names with robust connectivity related to Banyumas’ history, political figures and other figure names. The street names of heroes and religious figures are identified as national figures who are related and unrelated to Banyumas’ history. In contrast, the street names of the political figures and others came from local figures who had roles and struggled in Banyumas. In this research, to conclude, the street names in Banyumas Regency are formed diversely to commemorate and tribute the figures influenced by politics and cultural systems. Therefore, it can implicitly describe or explain the understanding of the past from generation to generation, so it becomes a cultural memory and representation embodied in Banyumas’ citizens.